Study of the Causes of Superficial Lymph Node Pathology in Gezira state Sudan 2010- 2015 - Elrhima, Omer Ahmed; Dawod, Ogail Yousif; Ageeb, Tellal Babiker; Elfaki, Mohammed; A. Elhasan, Talal Hashim; Ahmed Mirghani MD, Alia Mirghani; Saeed Khiery, Faiza Abdalla; Elhussein, Amar Babikir; Mustafa, Amna MohammedAli; E. Homeida, Husham; El Hassan, Lamyaa; H. Alfeel, Ayman (Journal of Neonatal Surgery, 2025)
Background: Lymphadenopathy is a complicated medical condition for the patient, the parent, and the physician. Various etiologies ranging from infectious to autoimmune as well as malignancy may cause lymphadenopathy. However, limited studies have focused on the clinicopathological significance of this condition. Objective: This study aims to investigate the spectrum of neoplastic and non-neoplastic diseases causing superficial lymph node enlargement in Gezira, Sudan, across different age groups and genders. It also correlates the findings with clinical data to determine the prevalence of various underlying conditions in Gezira State, Sudan. Method: The retrospective observational study was carried out in Gezira State, Sudan, from April 2010 to April 2015. We analyzed the data of 591 lymph node biopsy specimens that were received at the Medical Laboratory Department of Pathology, Faculty of Medicine, Gezira University. Results: Of the 519 superficial lymph node biopsies that were performed, 377 (72.6%) were from the cervical region, 65 (12.5 %) were from the axillary lymph nodes, 45 (8.7%) were from the inguinal region, and 32 (6.2 %) were from the supraclavicular lymph node, with male predominance affecting all age groups. Supportive lymphadenitis was found to be the most prevalent condition affecting the lymph node, followed by reactive hyperplasia and tuberculosis non-Hodgkin lymphoma, which was more common than Hodgkin lymphoma and metastasis. Conclusion: Lymph node involvement is far more prevalent in non-neoplastic diseases compared to neoplastic processes, with lymphadenitis being the predominant underlying pathological cause